Soundscape actions: A tool for noise treatment based on three workshops in landscape architecture - Gunnar Cerwén; Jacob Kreutzfeldt; Carola Wingren (Frontiers of Architectural Research, 2017)
This paper reports experiences from three workshops dealing with soundscape as a noise treatment approach in landscape architecture. The workshops were conducted between 2012 and 2016 in different contexts, for different purposes and with different participants. The paper describes the workshop approach employed and analyzes the proposals made by workshop participants to employ “soundscape action” as an operational tool in landscape architecture projects. Through a process of ‘keywording’ and clustering proposals from the workshops, 22 pragmatic soundscape actions emerged and are described on a general level. The paper then discusses the outcomes and experiences from the workshops and relates this to landscape architecture practice.